Relationship between breastfeeding and the incidence of diarrhoea in children aged 6-24 months - Manmeet Kaur Gurbachan Singh; Mahrani Lubis (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: Diarrhoea is still a global problem with high mortality. Children who are malnourished or have impaired immunity have the highest risk of diarrhoea. Exclusive breastfeeding in infants is known could protect the babies against diarrhoea.Objective: This study aims to determine the relationship between exclusive breastfeeding with the incidence of diarrhoea in children aged 6-24 months.Methods: This is an observational study where the data collected during August-November 2017 at Padang Bulan Primary Health Care. The subjects are a mother who has children between 6-24 months. The primary data was obtained through interviews using a validated structured questionnaire. The relationship between exclusive breastfeeding and the incidence of diarrhoea were analysed using Chi-square. Statistical analysis was performed in 95% coefficient interval (alpha=0,05).Results: Amongst 98 children, 53.1% are female. Children who have received exclusive breastfeeding were 53 children (54.1%). The number of children who had diarrhoea was 68.4% while many diarrhoea frequencies were 49%. Only 29 children (29.6%) had diarrhoea with exclusively breastfeeding, while 38 children (38.8%) had diarrhoea without exclusive breastfeeding. There is a relationship between exclusive breastfeeding to the incidence of diarrhoea in children aged 6-24 months (p= 0,002).Conclusion: There is a significant relationship between exclusive breastfeeding and the incidence of diarrhoea in children aged 6-24 months.